PENDIDIKAN SUFISTIK MULTIKULTURAL DALAM PENDIDIKAN KARAKTER DI INDONISIA - Muhammad Husni; Muhammad Hasyim (Universitas Islam Lamongan, 2019)
Multicultural sufistical education not only discusses the positive character, but also the negative one and how to handle it. This can provide a new perspective of the character education in Indonesia. A student needs to be aware of what he must avoid and how to avoid it in addition to staying away from it as early as possible. What is important to note is that, first, like worship, knowledge must also be with sincerity when studying it. Sincerity is a motive that makes knowledge meaningful. Second, knowledge is such an affiliation of worship. Third, learning dualism. Learning - in Sufistical education - is not only a process of finding knowledge. Character is only an attribute, and is not embedded in the soul. This kind of character education is unfilled with the spirit and goodness in the heart. So sufistical education - through the concept of psychology - provides a bridge to it. Character education should be littered with the process of penance in order to liven up the soul with awareness.